Confirmatory Factor Analysis of transformation leadership in the Graduate Students’ Perspectives - Pongharnyut, Surasek; Aungchuan, Kransuphamat; Chamnanprai, Jaroon (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The study entitled “Confirmatory Factor Analysis of transformation leadership in the Graduate Students’ Perspectives” aims to 1) study the attitude towards the transformation leadership in the graduate students’ perspectives, and 2 ) carry out the confirmatory factor analysis of transformation leadership in the graduate students’ perspectives. A questionnaire was used in data collection from those 481 graduate students in Bangkok while Frequency, Percentage, Means, Standard Deviation, Pearson’s Correlation Analysis, and Confirmatory Factor Analysis were utilized in data analysis. It is revealed that all values on the attitude towards the transformation leadership of those graduate students are at the high level. When arranged, it is found that the ideological influence is at the highest level (Mean = 3.60) followed by inspiration creation (Mean = 3.56), concern of individual (Mean = 3.54), and wisdom encouragement (Mean = 3.52) respectively. For the confrmatory factor analysis, it shows that 1) the transformation leadership on idealized inﬂuence is caused by the fact that the executives are concerned with morality and ethics in making their various decisions (λY = 0.77) the executives behave in the trustful ways (λY = 0.77) the executives and the staff together set up the plans and targets (λY = 0.77) 2) the transformation leadership on inspiration motivation is caused by the fact that the executives obviously inform all staff the policies and the working ways and also inspire the staff to work as of the policies (λY = 0.79) the executives inspire and encourage the staff to be more energetic in working in order to achieve their goals (λY = 0.75) the executives communicate or speak with all staff in positive ways (λY = 0.73) the executives focus on the creative solution for problems and settle the conflicts prior to their spreading out (λY = 0.73) 3) the transformation leadership on intellectual stimulation is caused by the fact that the executives promote the staff to have analytical thinking and enable them to solve the problems in the more creative ways (λY = 0.77) the executives support the staff in looking at the problems in different and varied dimensions (λY = 0.75) the executives support the staff in solving the problems in newer ways (λY = 0.73) 4) the transformation leadership on individualized consideration is caused by the fact that the executives assign the works in the putting the right man in the right job way (λY = 0.77) the executives listen and show that they understand the staff’s sayings (λY =0.77) the executives provide the staff the fruitful recommendations in developing their strength (λY = 0.76) the executives care in talking with the staff on their affairs individually in the friendly way (λY = 0.76). Article history : Accepted 16 October 2014 SIMILARITY INDEX = 0.00